Using Flash Cards to Improve the Vocabulary Mastery of XI Graders at SMA N 1 Ngaglik - Kezia Intan Permani; Made Frida Yulia; Dewi Rahayu (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
Vocabulary becomes one of the most essential aspects in learning English. However, since English was a foreign language in Indonesia, students had lack of vocabulary that made it difficult for them to learn English well. Teachers needed to help the students in mastering their vocabulary by using an interesting media. Therefore, this study aimed to investigate the use of flash cards as a learning media to improve students’ vocabulary mastery of XI Science 3 at SMA Negeri 1 Ngaglik. The participants of this study were thirty-two students from XI Science 3 at SMA Negeri 1 Ngaglik. Classroom Action Research was employed with 2 cycles. The data was collected using the pretest and posttest, and the questionnaires. The results showed that implementing flash cards in the learning process enhanced students’ vocabulary mastery. It could be proven based on the average of students’ scores which were 75.62 in the pretest, 94.68 in the posttest of cycle 1, and 98.12 in the posttest of cycle 2. Another thing, the results indicated that using flash cards gave many advantages for the students. By using flash cards, it was easy for students to remember the words, understand the meaning of the words, understand the synonym and definition of the words, and enhanced new vocabulary. Moreover, flash cards increased students’ motivation in learning vocabulary. From the results, it could be concluded that applying flash cards could improve students’ vocabulary mastery.